Exploring patterns of heart rate variability in major depressive disorder: A short-term study in Jaipur, Rajasthan - Sunidhi sharma; Sudhanshu Kacker; Neha Saboo (Journal of Clinical and Basic Research)
Background: Individuals suffering from major depressive disorder (MDD) frequently have abnormal heart rate variability (HRV) patterns. They have decreased HRV, which implies that there is less variance between subsequent heartbeats. Increased sympathetic nervous system activity (the "fight or flight" reaction) and decreased parasympathetic nervous system activity (the "rest and digest" response) are related to reduced HRV. This study investigates short-term HRV patterns in individuals with major depressive disorder. Methods: This observational study was conducted at RUHS College of Medical Sciences and Associated Hospitals, Jaipur, from July 2022 to January 2023, on a major depressive disorder population of either sex in the age group of 20-40 years. Cognitive functions were assessed using a questionnaire, and AD instruments recorded heart rate variability variables (time & frequency domain) using a digital physiograph (MLT004/ST). Data analyses were conducted using Microsoft Excel 2019. The Pearson correlation coefficient was calculated to determine the correlation, and a significance level of p<0.05 was utilized. Results: A positive association was detected between the Hamilton D (HAM D) score and high frequency and root mean square of the successive difference between normal heartbeats, which was significant (p < .05). In contrast, a significant negative correlation was seen between the Hamilton D score, heart rate, and mini-mental status (p < .05). Conclusion: This short-term investigation indicated different HRV patterns in MDD, defining a role in the diagnosis of depression. The detected relationships between HRV and depression severity imply that HRV monitoring could benefit the diagnosis and treatment of MDD. Further investigation is required to explore the long-term stability and clinical value of these HRV patterns.